The role of advisory bodies in the emergence of cross-cutting policy issues: comparing innovation policy in Norway and Germany - Christensen, Johan; Serrano-Velarde, Kathia (European politics and society, 2019)
The article examines the role of policy advisory bodies in the emergence of national innovation policy. Cross-cutting policy issues such as innovation policy pose unique challenges to governments. Given that they do not fit neatly within the purview of existing government departments, it is often unclear who is responsible for dealing with a given issue. Issues may go unaddressed or else be subject to competing initiatives from different departments. What role do policy advisory bodies play in addressing and advancing cross-cutting policy issues? The article examines how the issue of innovation policy was taken up and addressed by policy advisory bodies in two empirical cases: Norwegian ad hoc advisory commissions examining innovation policy during the period 1972-2016, and the German standing expert commission for science and innovation formed in 2006. The article finds that policy advice on innovation was adopted to a varying extent by the political-administrative system. It argues that this can be attributed to the organisation of advisory bodies and to the efforts of these bodies to establish connections and draw bridges across an entrenched political landscape.
Published online: 03 Sep 2018
Gesehen am 19.09.2018